Menakar Keadilan bagi Perempuan dan Anak dalam Kasus Poligami Liar pada Putusan Isbat Cerai di pengadilan Agama - Yanto Hasyim (SAKINAH: Jurnal Hukum Keluarga Islam, 2025)
Abstract: Unregulated polygamy defined as polygamy without court approval as stipulated in Law No. 1 of 1974 in conjunction with the Compilation of Islamic Law remains a critical issue in Indonesian family law, creating tension between legal certainty and substantive justice. This study examines the Situbondo Religious Court Decision No. 596/Pdt.G/2023/PA.Sit, which issued a niet ontvankelijke verklaard ruling against a petition for marriage validation (isbat nikah) and divorce in a case of unregistered polygamy (poligami siri). While the decision upholds legal certainty, it simultaneously denies women and children access to civil rights such as maintenance during the waiting period (nafkah iddah), post-divorce compensation (mut’ah), joint property division, and recognition of children’s legal status. Using a normative juridical approach reinforced by case analysis, this article finds that legal protection in cases of unregulated polygamy remains weak and tends to disadvantage vulnerable parties. Accordingly, the article proposes three alternative solutions: strengthening polygamy regulations with stricter sanctions, establishing compensatory mechanisms for second wives and children, and harmonizing religious and state laws. Thus, the study argues that reform of Indonesian family law should not merely focus on preventing unregulated polygamy but must also ensure minimum protection for women and children to achieve a balance between legal certainty and substantive justice. Keyword: Unregistered Polygamy, Isbat Divorce Ruling, Legal Certainty, Substantive Justice   Abstrak : Poligami liar yakni praktik poligami tanpa izin pengadilan sebagaimana diatur dalam Undang-Undang No. 1 Tahun 1974 jo. Kompilasi Hukum Islam menjadi problem serius dalam hukum keluarga Indonesia karena menciptakan ketegangan antara kepastian hukum dan keadilan substantif. Studi ini menelaah Putusan Pengadilan Agama Situbondo No. 596/Pdt.G/2023/PA.Sit yang memutus amar niet ontvankelijke verklaard terhadap permohonan isbat nikah dan cerai gugat dalam kasus poligami siri. Putusan ini memang menegakkan kepastian hukum, tetapi secara bersamaan menutup akses perempuan dan anak terhadap hak-hak keperdataan seperti nafkah iddah, mut’ah, harta bersama, dan perlindungan status anak. Dengan pendekatan yuridis normatif yang diperkuat analisis kasus, studi ini menemukan bahwa perlindungan hukum dalam praktik poligami liar masih minim dan cenderung mengorbankan pihak yang rentan. Untuk itu, tulisan ini menawarkan tiga alternatif solusi: penguatan regulasi poligami dengan sanksi yang lebih tegas, mekanisme kompensasi keperdataan bagi istri kedua dan anak, serta harmonisasi antara hukum agama dan hukum negara. Dengan demikian, penelitian ini menegaskan bahwa reformasi hukum keluarga Indonesia tidak cukup berhenti pada pencegahan poligami liar, melainkan harus menjamin perlindungan minimal bagi perempuan dan anak agar tercapai keseimbangan antara kepastian hukum dan keadilan substantif. Kata Kunci: Poligami Liar, Putusan Isbat Cerai, Kepastian Hukum, Keadilan Substantif.